Pengaruh BI-7 Day Reverse Repo Rate, Rasio Hasil Dividen, dan Rasio Pembayaran Dividen Terhadap Harga Saham pada Perusahaan LQ45 - Putra, Jefri Yanto Cahya; Yusdi Daulay; Komara (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aims to determine the effect of BI-7 Day Reverse Repo Rate, Dividend Yield, Dividend Payout Ratio, on stock prices. The variables studied were BI-7 Day Reverse Repo Rate, Dividend Yield, Dividend Payout Ratio, to Stock Price in LQ45 Company with quantitative method and the sample used was purposive sampling. Data processing used Microsoft Excel and SPSS Version 25 to analyze financial management, descriptive statistical analysis, classical assumption test, hypothesis testing, correlation coefficient analysis and coefficient of determination. The results showed that partially BI-7 Day Reverse Repo Rate and Dividend Yield had no effect on Stock Prices and Dividend Payout Ratio had a significant positive effect on Stock Prices, and simultaneously BI-7 Day Reverse Repo Rate, Dividend Yield, and Dividend Payout Ratio significant effect on stock price.